Some Recent Developments in Applied Econometrics: Dynamic Models and Simultaneous Equation Systems - Wallis, Kenneth F. (Journal of Economic Literature, 1969)
I am grateful to Meghnad Desai, Harry G. Johnson, Marcus H. Miller, Marc Nerlove, R. D. Terrell, J. J. Thomas, and the editors of this journalfor comment and discussion during the preparation of this paper. Although not explicitly referred to in the text, the more theoretical survey article on distributed lags by Griliches [28] also clarified my thoughts in a number of places. Errors of omission and comnmission are, as usual, my own responsibility.